Yudisialisasi Politik dan Sikap Menahan Diri: Peran Mahkamah Konstitusi dalam Menguji Undang-Undang - Bisariyadi, Bisariyadi (Jurnal Konstitusi, 2015)
In a review of the constitutionality of law or policy, the Constitutional Court can take an aggressive approach or choose to take self-restraint. Theoretical justification on the Court to change or made policy derived from the judicialization of politics. Global phenomenon indicates the shift of policy-making authority towards the judiciary. Consequently, policy makers shows resistence. Such conditions forced the Court to use a number of strategies to reduce political tensions between state institutions while at the same time the Court still protect the rights of citizens. The Court uses self-restraint approach to examine policies which in realm of legislative or executive discretion. This approach is referred to by the Court as an â€œopen(ed) legal policyâ€. This study elaborates on the actions carried out by the Indonesian Constitutional Court to test the constitutionality of law or policy, both in the application of the judicialization of politics nor in the judicial restraint approach. In reality, the Court uses both of these approaches on review the constitutionality of law and Â policy.